Social Prevention of Violent Extremism – European Practices and Macedonian Conditions - Bornarova, Suzana; Bogoevska, Natasha (Faculty of Philosophy, Ss. Cyril and Methodius University in Skopje, 2024)
Different practices in the prevention of violent extremism are present in European countries depending on the socio-political, historical, and cultural context. Dominant trends are those related to a combination of security and social protection approach, integrated services: social protection, health, education, employment, housing, and others, as well as various programs for prevention, de-radicalization, reintegration, and rehabilitation. In the Republic of North Macedonia, the gravity of this problem is insufficiently recognized, the measures taken are not systemic, but rather based on ad-hock interventions in emergency situations, while prevention is insignificant. The institutional capacities for dealing with this issue and its prevention are weak, while multi-sectoral cooperation, despite the introduced initiatives, is still underdeveloped. This paper will present the European trends in the social prevention and coping with the problem of violent extremism, as well as domestic conditions and challenges, with a focus on social protection.
Keywords: social prevention, violent extremism, European practices, social protection